Employee Service Programs and Productivity in Nigerian Public Organizations: A Study of Nigeria Port Authority, NPA Onne Port 2015-2024 - Leelee Johnson (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
The Nigerian Port Authority (NPA) Onne faces ongoing challenges of low productivity and bureaucratic delays, despite its vital role in trade and logistics. This study examined how employee service programs can enhance productivity in public organizations, focusing on NPA Onne from 2015 to 2024. Its objectives included exploring the relationship between organizational practices and employee service programs, assessing personnel development’s impact on service delivery, evaluating health and wellness initiatives, and identifying implementation challenges. The study aimed to develop standardized employee service programs aligned with NPA Onne’s strategic goals to boost motivation and efficiency, while strengthening health initiatives to reduce absenteeism. Based on Human Relations and Systems Theories, the research emphasized workplace relationships, employee welfare, organizational interdependence, and systemic integration. Key concepts included public organization, employee service programs, training, health initiatives, and organizational effectiveness. Using a survey design, structured questionnaires were distributed to 221 purposively selected staff out of 492 employees. Data were analyzed with mean scores and chi-square tests at a 0.05 significance level. Results revealed significant positive correlations between organizational practices and employee service programs, personnel development and service delivery, and health initiatives with overall organizational performance. It is recommended to develop standardized employee service programs aligned with NPA Onne’s strategic goals to enhance motivation and efficiency. The study concludes that well-implemented employee service programs can substantially improve organizational effectiveness.